Myeloid-derived suppressor cells inhibit natural killer cells in myelodysplastic syndromes through the TIGIT/CD155 pathway. Issue 1 (31st December 2023) - Yue, Jing; Li, Jiaojiao; Ma, Junlan; Zhai, Yan; Shen, Li; Zhang, Wei; Li, Lijuan; Fu, Rong
ABSTRACT: Objective: This experiment will explore the role of TIGIT/PVR signaling pathway in the pathogenesis of MDS immune tolerance through in vitro co-culture of NK cells and MDSC cells. Methods: Flow cytometry was used to detect the expression percentage of MDSCs and CD155 on MDSCs in the bone marrow of MDS patients and controls. The expression of NK cell surface receptors (NKG2D, NKp30, NKp46), secreted cytokines (perforin, granzyme B, CD107a, IFN-γ) and NK cell apoptosis rate were detected by flow cytometry to evaluate the effect of MDSCs on NK cell function. Results: The number of MDSCs in bone marrow of MDS patients was notably higher than that of the control group (8.39 ± 7.01 vs 2.31 ± 1.65, P = 0.0001). Compared with the control group, the expression of CD155 on MDSCs in MDS group was increased (31.81 ± 21.33 vs. 10.49 ± 6.53, P < 0.0001). After NK cells were co-cultured with MDSCs, NKG2D, NKp30, NKp46, CD107a, IFN-γ, perforin and granzyme B were decreased, and the NK function partially recovered after the addition of inhibitors. Conclusion: Compared with the normal control, MDSCs and CD155 on MDSCs were highly expressed in MDS patients. After co-culture with MDSCs, the expression of NK cells' surface receptors decreased, the secretion of cytokines decreased and the apoptosis rate increased. After blocking TIGIT/CD155 pathway, NK cell function was reversed, but NK cell apoptosis was not reduced.